2010
DOI: 10.1007/s10722-010-9631-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-locus EST-SSR markers for characterization of population genetic diversity and structure across ploidy levels in switchgrass (Panicum virgatum L.)

Abstract: Polyploidy, ploidal variation between populations, and aneuploidy within some populations complicate population genetic analyses in switchgrass. We report 21 genic-simple sequence repeat marker loci with single-locus disomic segregation in tetraploids and apparently tetrasomic inheritance in octoploids, thus allowing population genetic analyses across ploidy levels. Based on 472 individuals sampled over four tetraploid and eight octoploid cultivars, six to 55 alleles were detected per locus with an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…Generally, SSR markers with dinucleotide repeats were more polymorphic than trinucleotide repeats in several plant species, such as barley [42], rice [43], wheat [44], maize [45], and soybean [46]. In this study, of all scorable PPs in the preliminary screening, the dinucleotide repeat SSRs produced a significantly greater number of alleles than those with trinucleotide repeats (Table 1), which was consistent with previous studies in switchgrass [19,24,47]. However, in the final 48 PPs selected for duplex PCR, we found that both classes of SSRs were equally polymorphic.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, SSR markers with dinucleotide repeats were more polymorphic than trinucleotide repeats in several plant species, such as barley [42], rice [43], wheat [44], maize [45], and soybean [46]. In this study, of all scorable PPs in the preliminary screening, the dinucleotide repeat SSRs produced a significantly greater number of alleles than those with trinucleotide repeats (Table 1), which was consistent with previous studies in switchgrass [19,24,47]. However, in the final 48 PPs selected for duplex PCR, we found that both classes of SSRs were equally polymorphic.…”
Section: Discussionsupporting
confidence: 91%
“…ISSR [designed by the University of British Columbia (UBC set No. 9)], EST-SSR [62], and SCoT primer [45] sequences were aligned to the Panicum reference genome using the bl2seq blast program in NCBI (www.ncbi.nlm.nih.gov/BLAST/), which was designed to eliminate redundancies. Initially, four germplasms were used to screen marker primers [PI421999 (AM-314/MS-155), PI422006 (Alamo), PI642190 (Falcon), and PI642207 (70SG 016)].…”
Section: Methodsmentioning
confidence: 99%
“…PCR products were visualized following agarose gel (1.5 %) electrophoresis at 120Vfor 1.5 h in 1 × TBE buffer, followed by staining with GelRed (Tiangen Biotech, Beijing, China). The EST-SSR PCR consisted of a denaturation for 5 min at 94 °C then 35 cycles of 30 s at 94 °C, 30 s at 53–55 °C, and 2 min at 72 °C, with a final extension of 5 min at 72 °C [62] and products were visualized as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In nature, switchgrass plants with the same ploidy level can usually be easily intercrossed regardless of ecotype; however, hybrids between different ploidy levels are very rare [7,8]. Due to the ploidy barrier, genetic flow between upland and lowland ecotypes is limited, which has ultimately maintained a high level of genetic diversity in switchgrass germplasm [9][10][11][12][13][14]. Hybrid breeding, which has significantly impacted modern agriculture, is a method of creating new cultivars by crossing between genetic lines that have different backgrounds [15].…”
Section: Introductionmentioning
confidence: 99%